The Influence of Tik Tok Social Media on Student Learning Achievement at Pangkur 1 Elementary School, Pangkur Sub-District, Ngawi District Lesson Year 2023/2024 - Suwartiningsih, Suwartiningsih (STAI MA'ARIF MAGETAN, INDONESIA, 2023)
Tik Tok social media is an audio-visual media. This media is in the form of videos and photos made with various music. This media is a media that disseminates the creativity and uniqueness of each user. The use of the Tik Tok application, which is currently in great demand by the Indonesian people, especially among elementary school students, has made many negative and positive responses from the community. This study aims to determine the effect of using Tik Tok social media on the learning achievement of elementary school children. This type of research is qualitative research. The subjects of this research are class teachers, students, and guardians of students in class V. Data regarding the impact of using Tik Tok social media on student learning motivation was collected through observation, interviews, and documentation. The results of this study indicate that there is a very significant positive influence between Tik Tok Social Media on Learning Achievement. The use of Tik Tok social media has a positive impact on students such as increasing students' learning motivation including a high interest in learning, an urge to learn, and students' enthusiasm in participating in learning, encouraging students' creativity. However, excessive use of Tik Tok has a negative impact, namely students become lethargic to learn. In addition, learning outcomes decrease.